Do Reforms in Indonesia Affect Economic Growth? Learn Ten Years from 1999-2008 Period - Sariguna Johnson Kennedy, Posma (KnE Social Sciences, 2023)
Indonesia had observed a drastic drop in its economic growth in 1998 after the monetary crisis in mid-1997 but grew back slowly starting in 1999. Since then, the Indonesian economy has been moving slowly with low growth. From this phenomenon, this study aims to see which sectors positively influence economic growth. This research uses a quantitative method in which a model of economic growth is built as a linear regression model in a time series. The economic growth model is formed based on the neoclassical production function approach from the supply side. The economic reforms in Indonesia significantly impacted economic growth, although they had a negative effect in the first ten years. Investment growth and defense spending have a positive influence on national economic growth. Meanwhile, non-defense budget growth did not affect economic growth during the ten years before and after the reform. From these results, the best way to increase Indonesia’s economic growth is to create an atmosphere that encourages both foreign and domestic investors who want to invest in Indonesia with conditions that are conducive for investors. Keywords: economic growth, economic reforms, investment, government budget, defense expenditure